Analysis And Experimental Use Of CFRP Wrap Type On Flexible Reinforcement Of Concrete Beam - Andrew Agaton Pakpahan (Jurnal Mekintek : Jurnal Mekanikal, Energi, Industri, Dan Teknologi, 2022)
Now, reinforced concrete structures are more commonly used in buildings because they are cheaper than steel structures. However, many concrete structures are damaged due to planning errors and changes in building functions, so there are several ways to overcome this problem, by providing Fiber Reinforced Polymer (FRP) reinforcement. In this study, researchers discussed the comparison of the flexural strength of reinforced concrete beams using Fiber Reinforced Polymer (FRP). In this case, the researcher uses a Wrap-Type Carbon Fiber Reinforced Polymer (CFRP) as external reinforcement. The beam dimensions are 15 x 25 cm with a length of 320 cm. Based on the results of the analysis, the strength of the beam with CFRP is 1.877 times its initial strength. Based on the test results, the strength of the CFRP beam is 1.5 times its initial strength. Based on the results of this test.